Microscopic analysis of a primo vessel within a lymphatic vessel in a Sprague-Dawley rat - Felix Scholkmann; Yiming Shen; Pan-Dong Ryu (Translational Research in Anatomy)
Background: Numerous studies have documented the existence of an additional vascular system in mammals: the primo vascular system (PVS), consisting of primo vessels (PVs) and primo nodes. Methods: The PVS was investigated in five Sprague-Dawley rats. The dye Alcian blue was injected into the lymph node near the lumbar spine (lumbar lymph node) in one rat to stain the lymphatic tissue to determine whether the lymphatic vessels (LVs) contained PVs. Results: A PV (diameter: ∼30–50 μm) inside a LV (diameter: ∼120–200 μm) was identified near the inferior vena cava. Microscopy images of this specimen are shown in this report and analysed. A reference is given to a detailed guide on how to find, extract and analyse the PVs within the LVs of rats. Conclusions: The case report documents a PV inside an LV and shows that LVs can contain a secondary vessel that could be identified as a PV and part of the PVS.